2018
DOI: 10.1016/j.acalib.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Long Nav or Short Nav?: Student Responses to Two Different Navigational Interface Designs in LibGuides Version 2

Abstract: A B S T R A C TThis study used two successive phases of usability testing to evaluate two different versions of a Communication 430 course LibGuide. The first version of this guide had a longer, more visually complex navigation menu, with more course-related research information directly accessible through this menu. The second version had a shorter, less complex menu that offered less directly accessible information. Twenty-four of the 33 students enrolled in the class (73%) tested either one version or the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Their study was an excellent example of providing a format that would assist users with comprehending the content instead of having to understand the design itself. 15 For this study, the RGRT adopted the five-user assumption commonly practiced among user experience professionals. The five-user assumption posits that, as you run usability testing, each additional user after the first will find usability problems already discovered by an earlier user in addition to discovering new problems.…”
Section: Redesigning Research Guides 6 Mcclure Hess and Marsicanomentioning
confidence: 99%
“…Their study was an excellent example of providing a format that would assist users with comprehending the content instead of having to understand the design itself. 15 For this study, the RGRT adopted the five-user assumption commonly practiced among user experience professionals. The five-user assumption posits that, as you run usability testing, each additional user after the first will find usability problems already discovered by an earlier user in addition to discovering new problems.…”
Section: Redesigning Research Guides 6 Mcclure Hess and Marsicanomentioning
confidence: 99%
“…24 This ideology is in alignment with cognitive load theory, which asserts that LibGuides should be as concise and intuitive as possible and, as a result, students will not have to exert extra effort in understanding how to navigate the guide itself but can, instead, focus their energies on analyzing and understanding the information provided on and through the guide. 25…”
Section: Support For Templatesmentioning
confidence: 99%
“…Following the emergence of LibGuides as a commonly-used platform, a number of studies examining different aspects of their effective design and use have appeared (e.g., Adebonojo, 2010;Gonzalez & Westbrock, 2010;Ouellette, 2011;Sonsteby & DeJonghe, 2013). Nevertheless, Bowen, Ellis, and Chaparro (2018) have observed that while usability testing of LibGuides has been widely discussed among the librarian community, there is a need for further investigation. With a diverse range of libraries using LibGuides internationally, additional data from different types of institution will help in the development of best practices in subject guide design on this platform.…”
Section: Literature Reviewmentioning
confidence: 99%